Analysis of employee data system at the department of public works development and spatial plan of the province of south sumatera - Aisya Idah Triputri Paskalita; Jimmie (International Journal Cister, 2022)
In the current era of globalization which is marked by various kinds of changes in aspects of human life, especially changes in developments in the field of information technology which is growing rapidly from year to year. Developments in this field aim to improve an effective and efficient data collection system, both in a company and in government. To implement the data collection system, a company and government really need a program in managing employee/employee data that is more effective to maintain the smooth operation of a company and government. The procedure for processing employee data at the Public Works Department of Highways of South Sumatra Province has been supported by technology, but its use is only limited to processing data using application packages in Microsoft Office, namely Excel and Word. Basically the application can meet the need for data processing required but there are some things that are lacking. The system that runs on the Personnel Subdivision of the Public Works Department of Highways still has problems in terms of storing employee data and other reports. Until now in the storage of a data is still classified as semi-computerized. Therefore we need a computerized data storage concept so that various difficulties related to employee data processing can run efficiently.